Pengaruh Perencanaan Pajak, Sales Growth, dan Ukuran Perusahaan Terhadap Manajemen Laba - Anggreani, Vemyta; Arfianti, Rizka Indri (Jurnal Manajemen, 2024)
The income statement in the financial report is one of the important indicator for shareholders and creditors to obtain information on profit and financial performance of a company and make investment decisions in a company. Profit reflects that the company has achieved good financial performance. Managers will carry out earnings management practices to influence several parties who have different interests in a company with the aim of ensuring that the financial reports presented are in line with the expected profit targets. This research aims to prove whether tax planning, sales growth, and firm size influence earnings management. The theories underlying this research are Agency Theory, Positive Accounting Theory, and Signalling Theory. This study processed 147 samples of consumer non-cyclical sector registered on Indonesia Stock Exchange in 2020-2022. In concluding this research, sales growth and firm size to state that both have a positive influence on earnings management, and that there is insufficient evidence that tax planning has a positive influence on earnings management.